Periodontists' Knowledge, Perception, and Professional Behaviour Regarding Patients' Psychosocial Factors and Treatment Outcomes in Nepal - Adhikari, Khushbu; Shrestha, Sajeev; Baral, Dharanidhar (Journal of Nepalese Society of Periodontology and Oral Implantology, 2022)
Introduction: Psychosocial factors when present in patients affect their treatment decision making and prevent them from seeking dental care. It also plays an important role in predicting the severity of pain, periodontal disease, and wound healing. Periodontists can provide the best treatment plan but may fail to obtain expected outcomes as patients may not follow the recommendation made by them. Objective: To assess knowledge, perception and professional behaviour of Periodontists’ regarding patients’ psychosocial factors and responses to periodontal treatment in Nepal. Methods: A descriptive, online cross-sectional survey using Google Forms was conducted among the Periodontists practicing in Nepal from June 2021 to August 2021. A questionnaire developed by Kloostra et al. was modified according to our practice setup and used for the survey. A total of 48 periodontists practicing in the country responded to the questionnaire. Results were analysed using SPSS v.11.5. A p value <0.05 was considered statistically significant at 95% confidence interval. Results: A significant difference in response for relation with perceived pain, perception of pain, wound healing and wound integrity between stress and depression was observed in this study. There was a significant difference (P=0.001) in preparedness for communicating with patients after postgraduate training and after undergraduate training. Conclusions: Periodontists agreed that there is role of stress, anxiety and depression in their patients’ responses to treatment. The lack of preparation at dental school to consider impact of psychosocial factors when treating patients is highlighted.